2021
DOI: 10.5430/ijfr.v12n3p43
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Tax Revenues: Empirical Evidence From Jordan

Abstract: The purpose of this study is to identify the determinants of tax revenues (TXR) in Jordan. The study covered the period (1990-2019) and used ARDL Bound test for co-integration, ARDL Long Run form, and ARDL Error Correction regression to examine the study hypotheses. The results of the bound test and co-integration equation (CointEq1) shows that there exists a long run relationship between (INDUST, LPCI, FD, FAID, GE, OPEN) and (TXR) in Jordan. The analysis results revealed that per capita GDP, fiscal deficit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The results showed that there is a statistically significant direct effect at the level of significance of 10% of the real GDP per capita on tax revenues, as an increase in the per capita real GDP by one unit leads to an increase in tax revenues by (0.001) units with constant factors. this is consistent with the study of each of (Castro, 2014;Gustofan, 2021;Teref, 2018;Alqudah, 2021;Tujo, 2021). The null hypothesis was rejected, which states that "there is no statistically significant effect of real GDP per capita on tax revenues at the significance level (α≤0.10).…”
Section: Estimating the Study Modelsupporting
confidence: 91%
See 2 more Smart Citations
“…The results showed that there is a statistically significant direct effect at the level of significance of 10% of the real GDP per capita on tax revenues, as an increase in the per capita real GDP by one unit leads to an increase in tax revenues by (0.001) units with constant factors. this is consistent with the study of each of (Castro, 2014;Gustofan, 2021;Teref, 2018;Alqudah, 2021;Tujo, 2021). The null hypothesis was rejected, which states that "there is no statistically significant effect of real GDP per capita on tax revenues at the significance level (α≤0.10).…”
Section: Estimating the Study Modelsupporting
confidence: 91%
“…Unit, ceteris paribus. This is consistent with the study of each of (Teref, 2018;Alqudah, 2021) and contradicts the study of each of (Castro, 2014;Tujo, 2021). The null hypothesis was rejected, which states, "There is no statistically significant effect of the added value of the agricultural sector on tax revenues at the level of significance (α≤0.05).…”
Section: Estimating the Study Modelsupporting
confidence: 76%
See 1 more Smart Citation
“…It aids the government in stabilization of national economy, the allocation of money, and the distribution of income and wealth among the people (Al-Qudah, 2021, Amirthalingam, 2020. Tax income supports citizens through providing social services such as schools, hospitals, roads, housing, and transportation, in addition to being a key source of revenue for the government (Hasan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Developed countries collect higher tax revenue because they employ their tax bases more effectively (Sharma, 2015). In impoverished countries, they collect an average of 16.5% (Al-Qudah, 2021). The average tax income to GDP ratio in SSA nations is less than the UN's (UN) 20% objective for funding social and economic activities (Amirthalingam, 2020).…”
Section: Introductionmentioning
confidence: 99%